IMPLICATIONS OF EARLY MARRIAGE ON HEALTH AND HOUSEHOLD HARMONY - Alwi Jaya; Sumarni; Gustika Sandra; Tarmizi (Publikasi Indonesia, 2023)
This research aims to determine the implications of early marriage on the health aspects of married couples and household harmony. This research is library research through data collection and analysis carried out qualitatively. The data source in this research is primary data, namely data obtained through library materials or relevant research results. The research results show that there are several factors that cause the phenomenon of early marriage, namely, individual factors, economic factors, educational factors, accident factors and community habits. Early marriage can have an impact on aspects of education and self-development which become hampered, trigger Domestic Violence (KDRT), increase the risk of neglect, sexual and reproductive health problems, as well as sexual and reproductive health problems. For this reason, it is hoped that early marriage does not occur by knowing what impacts it has and becoming an asset for society, especially in their respective families, so that they can prevent early marriage.